Measuring climate resilience by linking shocks to development outcomes. (8th August 2020) - Barrett, Sam; Brooks, Nick; Quadrianto, Novi; Anderson, Simon; Nebsu, Bayu
ABSTRACT: Adaptation finance addresses the effects of climate variability and change on development and physical insecurity. Yet, adaptation has proven difficult to systematically measure and assess, resulting in a lack of coherent and comparable evidence to learn about good adaptation practice. Measurement has become even more challenging since the integration of resilience into policy framings. Measuring climate resilience requires evidence of resistance to, and recovery from, shocks and stresses. But resilience of what, to what seldom guides the design of assessments. Researchers tend to use proxy indicators and aggregated units of analysis that cloud the relationships under study, and crucially, leave unclear the interactions between climate and development. This viewpoint documents these common barriers to progress in the field. It then outlines two methods for practitioners and researchers to link climate shocks and stresses to climate-sensitive development outcomes as a key first step to research and evaluation design. Both methods enable prediction of expected levels of development outcomes, given the extent of climate shocks and stresses, which is then comparable with actual levels achieved under climate resilience interventions. The product is standardized and comparable metrics to learn about the performance of climate adaptation policymaking and resilient development programming.